The differential role of IL-33 and IL-38 in prostate cancer, contradictory roles - Ban, Runfen; Gao, Shanshan; Zhou, Bin; Bao, Shisan (Frontiers in Immunology, 2025)
Prostate cancer (PCa) is still as a major cause of morbidity and mortality in men at the global level, highlighting the necessity for improved diagnostic and therapeutic strategies beyond current PSA screening limitations. This mini-review focuses on the complex and often opposing roles of two key cytokines, IL-33 and IL-38, within the tumour microenvironment and their implications for host immunosurveillance in PCa. Intra-tumoral IL-33 expression is significantly reduced in PCa tissues and correlates with aggressive disease features such as higher Gleason scores and lymphatic metastasis, suggesting an inherent anti-tumour function. Such a protective role may be mediated via the ST2/NF-κB signalling pathway and the recruitment of lymphocytes into the tumour microenvironment. However, a paradoxical increase in circulating IL-33 levels in PCa patients hints at complex systemic compensatory mechanisms or differential compartmental regulation. In contrast, intra-tumoral IL-38 exhibits markedly elevated expression in PCa compared to benign prostatic hyperplasia and non-cancerous tissues. This increased IL-38 correlates with tumour severity, advanced TNM stages, and poorer overall survival, indicating a pro-tumoral role. Mechanistically, IL-38 appears to inhibit CD8+ cytotoxic T cell infiltration and potentially promotes immunosuppression through the upregulation of regulatory T cells (Tregs), thereby facilitating tumour progression. The contrasting expression patterns and clinicopathological associations of IL-33 and IL-38 highlight their potential as novel biomarkers for PCa diagnosis and prognosis. Further comprehensive investigation, including multi-centre studies across diverse populations, functional in vitro and in vivo analyses, and exploration of their therapeutic targetability, is crucial to translate these findings into effective precision medicine strategies for PCa patients.